The use of Lewis acid AlCl3 as a promoter in the Pd-complex catalytic system of the cyclohexene hydroethoxycarbonylation reaction - Kudaibergenov, N.Zh.; Shalmagambetov, K.M.; Vavasori, A.; Zhaksylykova, G.Zh.; Kanapiyeva, F.M.; Almatkyzy, P.; Mamyrkhan, D.B.; Bulybayev, M. (KU Publ., 2021)
This paper presents the results of detailed studies of the possibility of using Lewis acid AlCl3 as a promoter of the catalytic three-component system PdCl2(PPh3)2–PPh3–AlCl3 in the hydroethoxycarbonylation reaction of cyclohexene at low carbon monoxide pressures (2.5 MPa). As a result a high catalytic activity of the threecomponent system was established and the reaction proceeds regioselectively with the formation of ethyl ether of cyclohexanecarboxylic acid. The optimal conditions of the process have been elaborated (molar ratio of the starting reagents [Cyclohexene]:[Ethanol] = 1:1; molar ratio of the components of the catalytic system = = [PdCl2(PPh3)2]:[PPh3]:[AlCl3] = 1:6:9; carbon monoxide pressure PCO = 2.5 MPa; process temperature T = 120 °C and reaction time τ = 5 h) at which the target product yield reaches 80.7 %. To identify the obtained ethyl ester of cyclohexane carboxylic acid gas chromatographic analysis and mass- and IR- spectra were carried out. Based on the data obtained, a possible mechanism of the reaction route of cyclohexene carbonylation with carbon monoxide and ethanol in the presence of the three-component system PdCl2(PPh3)2–PPh3–AlCl3 is proposed and discussed.
Циклогексенді гидроэтоксикарбонилдеу реакциясының Pd-комплексті каталитикалық жүйесінде AlCl3 Льюис қышқылын промотор ретінде қолдану
Использование кислоты Льюиса AlCl3 в качестве промотора в Pd-комплексной каталитической системе в реакции гидроэтоксикарбонилирования циклогексена
Keywords: cyclohexene; carbon monoxide; Pd-complex catalysts; phosphine ligands; aluminium (III) chloride; hydroalkoxycarbonylation; ethyl ester of cyclohexanecarboxylic acid; “Hydride” mechanism